2000
DOI: 10.1111/j.1752-1688.2000.tb04248.x
|View full text |Cite
|
Sign up to set email alerts
|

SOLUBLE SUGAR COMPOSITION OF POND‐CYPRESS: A POTENTIAL HYDROECOLOGICAL INDICATOR OF GROUND WATER PERTURBATIONS1

Abstract: Pond-cypress, a deciduous conifer, is a dominant canopy species in depressional wetlands of the southeastern Coastal Plain (SCP). Extensive premature decline and death of pond-cypress trees in central Florida have been attributed to hydroperiod alterations due to excessive withdrawals of ground water from the Floridan aquifer. One factor identified in the decline process is basal decay, which may be related to the presence of Botryosphaeria rhodina and Fusarium species (nonaggressive, facultative fungal pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The most abundant carbohydrates detected in leaves of the four genotypes were glucose, fructose, and sucrose, which was in accord with Mononen et al (2004). The water-deficit-induced increase in total foliar carbohydrates, polyols, and organic acids has been reported as an indicator of osmotic adjustment during water-deficit stress in many woody and herbaceous species (Arndt et al, 2001;Bacchus et al, 2000;Malinowski and Belesky, 2000;Pankovic et al, 1999;Patonnier et al, 1999;Richardson et al, 1992). Osmotic adjustment could help maintain plant turgor and facilitate physiological activities (Hare et al, 1998;Malinowski and Belesky, 2000), which was not previously observed in birch genotypes in response to imposed water deficit (Ranney et al, 1991).…”
Section: Discussionmentioning
confidence: 57%
“…The most abundant carbohydrates detected in leaves of the four genotypes were glucose, fructose, and sucrose, which was in accord with Mononen et al (2004). The water-deficit-induced increase in total foliar carbohydrates, polyols, and organic acids has been reported as an indicator of osmotic adjustment during water-deficit stress in many woody and herbaceous species (Arndt et al, 2001;Bacchus et al, 2000;Malinowski and Belesky, 2000;Pankovic et al, 1999;Patonnier et al, 1999;Richardson et al, 1992). Osmotic adjustment could help maintain plant turgor and facilitate physiological activities (Hare et al, 1998;Malinowski and Belesky, 2000), which was not previously observed in birch genotypes in response to imposed water deficit (Ranney et al, 1991).…”
Section: Discussionmentioning
confidence: 57%
“…The preliminary research on young pond-cypress trees by Bacchus et al (2000;see also Bacchus et al, in review) suggests that spectral analysis of pond-cypress branch tips using the NIRSystems  6500 can provide a more scientifically-based and sensitive means of detecting responses to groundwater perturbations than the current approaches. Spectral analysis of pond-cypress from natural stands has not been reported previously.…”
Section: Developing a New Approachmentioning
confidence: 95%
“…As a first step to developing a new approach for early detection of stress from prolonged water deficits, Bacchus et al (2000) evaluated differences in composition of non-structural soluble sugars in branch tips from young pond-cypress subjected to controlled water stress conditions in a growth chamber experiment. An annual cycle of temperature, humidity and day length was simulated for the central Florida area where the trees originated.…”
Section: Developing a New Approachmentioning
confidence: 99%
“…Examples of adverse environmental impacts throughout the extent of the FAS associated with pirated water from aquifer withdrawals (mechanical and nonmechanical) and injections, including ASR, have been described by Bacchus (1998;2001;2002;2006;2007); Bacchus and Barile (2005); Bacchus and Brook (1996); Bacchus et al (2000;2011;2015a Sonenshein and Hofstetter (1990);and Wilcox, Solo-Gabriele, and Sternberg (2004). This large body of literature has identified many categories of adverse impacts.…”
Section: Adverse Environmental Impacts Associated With Pirated Water mentioning
confidence: 99%
“…The irreversible degradation of habitat leads to declines in native wildlife (Bacchus, 2000). Examples of these and other adverse environmental impacts in the FAS are described in Bacchus (1998;2001;2006;2007) and Bacchus et al (2000;2011;2015a Table 5 were identified in the 2015 SWAP as particularly relevant to aquatic species.…”
Section: Adverse Environmental Impacts Associated With Pirated Water mentioning
confidence: 99%